UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS X PADA MATA PELAJARAN AKIDAH AKHLAK MELALUI MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI DI MADRASAH ALIYAH NEGERI PAMEKASAN - Saiful Hadi; Hariri Al Gazir; Suwantoro Suwantoro; Mahrus Miyanto (Dewan Pendidikan Pamekasan, 2023)
This research was motivated by the low learning motivation of students in the Islamic Religious Education learning process on the Aqidah Akhlak subject at MAN Pamekasan. The research method uses a qualitative approach while the type of research is Classroom Action Research (PTK). The research location is MAN Pamekasan. Data sources were obtained from the Head of the Madrasah, the teacher in charge of the Class The stages in data analysis include, (1) Data Reduction, where in reducing this data the researcher carries out checking, grouping and coding, (2) Data Presentation, (3) Conclusion and Data Verification. The research results showed that in cycle I it could be concluded that; First, the way to increase the learning motivation of class Second, the way to increase the learning motivation of class The score results in Cycle I were 75% and Cycle II 88%. Third, factors that support the process of learning moral beliefs through information technology-based learning media are adequate facilities and infrastructure, teacher creativity, and students' familiarity with information technology media. The factors that hinder this include interference with the media, teacher creativity and the condition of students who are not ready to accept learning.